Seismic collapse risk assessment and probabilistic sensitivity analysis of braced frames under near-fault earthquakes - Sonwani, Jeet Kumar, author; Jia, Gaofeng, advisor; Mahmoud, Hussam, advisor; Arneson, Erin, committee member (Colorado State University. Libraries, 2019)
Special concentrically braced frames (SCBFs) are popular structural systems used in regions with high seismicity. For SCBFs located in regions close to earthquake faults, they may be subject to near-fault ground motions, often characterized by forward directivity pulse with long periods. These near-fault pulses could impose additional seismic demands on structures and increase the risk for structural collapse. Currently, there is limited research on the seismic collapse risk of SCBFs under near-fault earthquakes. To accurately assess the seismic collapse risk of structures under near-fault ground motions, the seismic hazards and the near-fault characteristics and the associated uncertainties need to be properly quantified. To this end, this research investigates the seismic collapse risk of SCBFs under near-fault earthquakes focusing on two typical SCBFs (i.e., SCBF with Chevron bracing and SCBF with Cross bracing). To assess the seismic collapse risk, a general simulation-based risk assessment framework is used. To quantify the large variability and uncertainty associated with the seismic hazard, stochastic ground motion (SGM) model is used where the near-fault pulse characteristics are explicitly incorporated. The uncertainties in the SGM model parameters (including the near-fault pulse characteristics) are addressed through appropriate selection of probability distribution functions (PDFs). To accurately predict the occurrence of collapse, numerical models capable of capturing the nonlinear and collapse behavior are established for the two braced frames and used in nonlinear time history analysis subject to the stochastic ground motion excitations. Stochastic simulation is used to propagate the uncertainties and evaluate the resulting multidimensional risk integral. Probabilistic sensitivity analysis is carried out to investigate the importance of each (or groups of) uncertain model parameters within the SGM including the near-fault pulse characteristics towards the seismic collapse risk of the two braced frames. The results indicate that near-fault ground motions could lead to significant increase in the seismic collapse risk of SCBFs and need to be properly considered when designing such structures.